Optimizing Intravenous to Oral Medication Conversion: A Pharmacist’s Perspective - Kapil Kumar Sharma (Innovations in Pharmacy Planet, 2014)
Intravenous (IV) to oral (PO) medication conversion is a crucial strategy in hospital settings to enhance patient care, reduce costs, and minimize complications associated with prolonged IV therapy. This review explores the rationale, criteria, and best practices for optimizing IV to PO conversion from a pharmacist’s perspective. Effective conversion requires careful assessment of drug bioavailability, patient stability, and clinical conditions. Several drug classes, including antibiotics, analgesics, proton pump inhibitors, and cardiovascular agents, have well-established oral alternatives that ensure therapeutic efficacy. Pharmacists play a central role in evaluating eligibility for conversion, developing hospital-wide protocols, educating healthcare teams, and monitoring post-switch outcomes. Despite its benefits such as decreased hospital stays, reduced risk of IV-related infections, and improved patient comfort challenges like clinician resistance and variability in patient response remain. Case studies highlight the successful implementation of pharmacistdriven automatic substitution policies in improving healthcare efficiency. Advancements in artificial intelligence and decision-support tools further strengthen IV to PO conversion programs. Standardized protocols, continuous pharmacist intervention, and interdisciplinary collaboration are essential for maximizing the benefits of IV to oral therapy. This review underscores the need for ongoing research and policy development to optimize medication conversion and improve patient safety.